Chemical vapour deposition of diamond for dental tools and burs - Ahmed, Waqar; Sein, Htet; Jackson, Mark J.; Rego, Christopher; Phoenix, David A.; Elhissi, Abdelbary; Crean, St. John (SpringerBriefs in Materials,, 2014)
This volume presents chemical vapour deposition of diamond films for application in cutting tools, microdrills, dental burs and surgical tools. It examines various deposition techniques, discusses mechanisms of diamond growth and their impact on cutting tool life and performance.